Identification and management of financial business risks at machine-building enterprises in Ukraine as a component of ensuring economic security - Khatser, Maxim (Management and Entrepreneurship: Trends of Development, 2025)
The article is devoted to the formation of new scientific solutions to increase the efficiency of identifying and managing financial business risks at machine-building enterprises in Ukraine. It has revealed the scientific and practical necessity of enhancing the efficiency of financial business risk management at Ukrainian machine-building enterprises, in the context of ensuring a sufficient level of economic security and resilience for machine-building business entities in the country. The aim of the article is to identify ways to improve the efficiency of financial business risk management at machine-building enterprises in Ukraine within the framework of ensuring the economic security of machine-building business entities in the country. Methodology: A set of general and specific methods has been applied at both empirical and theoretical levels. These include the method of content analysis for the study of scientific issues in the field of financial business risk management, as well as for determining the essence of the terms "risk" and "financial risk of the enterprise"; the analysis method for determining trends and features of financial business risk management at machine-building enterprises in Ukraine; the synthesis method for determining the relationship between financial business risks, economic security, resilience, anti-crisis management (anti-crisis financial management - adaptive management) at the enterprise; methods of induction and deduction for developing a scheme of managerial influences aimed at increasing the efficiency of financial business risk management at machine-building enterprises in Ukraine, as well as procedures for assessing financial business risks for Ukrainian machine-building business entities; and the methods of systematization, grouping, and logical generalization to organize information and formulate the conclusions and scientific proposals of the article. Results: ways to improve the efficiency of financial business risk management at machine-building enterprises in Ukraine within the framework of ensuring the economic security of machine-building business entities in the country. JEL Classification: L20, L64, M21